Synthesis Of Hydroxyl-Alkoxylate Fatty Esters From Methyl Esters Of Palm Fatty Acid Distillate And Their Potential Application As Lubricant-Based Stock - Lee, Pei Luan (2010)

(untitled)
Methyl ester of palm fatty acid distillate (PFAD-ME) was used to synthesize hydroxyl-alkoxylate fatty esters via epoxidation of its double bonds in the fatty acid chains and alcohol oxirane group cleavage reaction. The effects of reaction temperature, molar ratio of the hydrogen peroxide to PFAD-ME unsaturation and molar ratio of the formic acid to the unsaturation on the epoxidation of PFAD-ME were studied. The study showed that more than 98% conversion of the unsaturation to epoxide ring moiety could be achieved within 3 hours of reaction period without any catalyst with the molar ratio of unsaturation: formic acid: hydrogen peroxide of 1:1:4 respectively and reaction temperature of 50 °C. For the epoxy ring opening process, optimization was also studied by changing various reaction parameters. The amount of boron trifluoride ethyl etherate, the catalyst used for the ring opening reaction of the epoxidized PFAD-ME with 2-ethyhexanol, was 0.75 % (wt/wt). The ring-opening reaction was carried out at 70 °C for 3 hours.Other primary alcohols such as methanol, ethanol, n-propanol, n-butanol, iso-butanol, n-pentanol, and n-hexanol were also used for the ring opening reaction of the epoxidized PFAD-ME. The viscosity of the products improved by around 85% as compared to those of the epoxidized PFAD-ME and original PFAD-ME. Although their pour points were similar to that of the PFAD-ME of which was 18 °C, the cloud point of the hydroxyl-alkoxylates decreased as the carbon chain of the alcohol used was increased. The RBOT time increased from 27.9 min for the PFAD-ME to 120.4 min for epoxidized PFAD-ME indicating that introduction of the epoxy group in the PFAD-ME increased its polarity. However, oxidation stability of the hydroxylalkoxylate fatty ester after reacting with 2-ethylhexoxyl groups was slightly better than that of the PFAD-ME. When the thermal stability of the products was examined using TGA/DTG, it was observed that the decomposition temperature increased from 290 °C for PFAD-ME and epoxidized PFAD-ME to around 390 °C for the hydroxylalkoxylate samples.